Exploring the antecedents of mobile payment service usage: Perspectives based on cost–benefit theory, perceived value, and social influences. Issue 1 (2nd January 2020) - Lin, Kuan-Yu; Wang, Yi-Ting; Huang, Travis K.
Abstract : Purpose: The number of smartphone users has increased with the maturity of mobile networks, which has not only led to a new lifestyle but has also facilitated the development of mobile application services. Smartphones are regarded as essential communication devices. Currently, diverse groups of people are considering using mobile payment services. Thus, the motives for using mobile payment as well as individual motives for continuing usage are of great research interest. The purpose of this paper is to examine the behavioral motivations underlying individual intentions to continue using mobile payment. Design/methodology/approach: To explore the factors affecting the intention to use mobile payment services, this study constructed a theoretical framework based on cost-benefit theory that also considers social influences to form an integrated research model that explains the intentions of individuals to use mobile payment services. Online questionnaires were used to evaluate individuals with experience using mobile payment services. A total of 302 questionnaires were collected. Structural equation modeling was employed to assess the relationships among factors included in the research model. Findings: Perceived value, social norms and social self-image played crucial roles in the intention to use mobile payment services. Furthermore, perceived benefits (relative advantage and service compatibility) and perceived costs (security risks and perceived fees) determined users' perceived value. Social self-image positively affected users' perceived value; in the context of a mobile-oriented information system, the ability of a mobile payment service to satisfy a user's demands with respect to social self-image influenced the user's perceived value of using such services. Originality/value: This study contributes to a theoretical understanding of factors that explain users' intention to use mobile payment services.